On (1,2)* b-Open Functions and (1,2)* b-Closed Functions In Bitopological Spaces - Mahmood, Sabiha I; Hamdi, Sanaa (Al-Nahrain Journal of Science, 2018)
The main goal of this paper is to create special type of open and closed functions in bitopological spaces namely, quasi (1,2)* b-open functions and quasi (1,2)* b-closed functions. Also, we give some properties and equivalent statements of this concept.